Sunscreen Activity Testing of Robusta Coffee (Coffea cenephora ex froehner) Leave Extract and Fractions - Kiki Mulkiya Yuliawati; Esti Rachmawati Sadiyah; Riski Solehati; Aldi Elgiawan (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Coffee leaves are part of a plant that has not been optimally utilized. The purpose of this study was to explore the potential use of coffee leaves to help maintain skin health. Extraction method was carried out with maceration method using 70% ethanol solvent. Fractionation process was carried out by Liquid-Liquid Extraction method, using different solvents to accumulate the n-hexane, ethyl acetate [A1] and methanol fractions. Activity testing was carried out on all samples at concentrations of 50, 100 and 150 ppm including measurements of Sun Protecting Factor (SPF), Erythema and Pigmentation Transmittance Percentages (%Te [A2] and %Tp[A3] ) using UV-visible spectrophotometry at 290 and 400 nm wavelengths. The results showed that the ethyl acetate [A4] fraction at a concentration of 150 ppm had a higher potential as a sunscreen than other samples with SPF value of 19.82; %Te [A5] 10.96 and %Tp [A6] 18.14 and included in the category of fast tanning sunscreen.Keywords: coffee leaves, sunscreen, sun protecting factor, erythema, pigmentation